Acute kidney injury associated to COVID-19 leads to a strong unbalance of circulant immune mediators. (September 2022) - Medeiros, Thalia; Guimarães, Gabriel Macedo Costa; Carvalho, Fabiana Rabe; Alves, Lilian Santos; Faustino, Renan; Campi-Azevedo, Ana Carolina; Peruhype-Magalhães, Vanessa; Teixeira-Carvalho, Andréa; de Souza Gomes, Matheus; Rodrigues do Amaral, Laurence; Martins-Filho, Olindo Assis; Lugon, Jocemir Ronaldo; et al.
Highlights: Severe COVID-19 increases the risk for AKI, and consequently the risk for death. COVID-19 associated AKI leads to higher and sustained levels of immune mediators. These alterations occur independently of death in AKI patients. CCL-2 and CXCL-10 show a good predictive value regarding AKI development. In AKI patients, immune mediators are correlated with SARS-CoV-2 viral load. Abstract: Background: Severe cases of coronavirus disease 2019 (COVID-19) have increased risk for acute kidney injury (AKI). The exacerbation of the immune response seems to contribute to AKI development, but the immunopathological process is not completely understood. Objectives: To analyze levels of circulant immune mediators in COVID-19 patients evolving with or without AKI. We have also investigated possible associations of these mediators with viral load and clinical outcomes. Methods: This is a longitudinal study performed with hospitalized patients with moderate to severe COVID-19. Serum levels of 27 immune mediators were measured by a multiplex immunoassay. Data were analyzed at two timepoints during the follow-up: within the first 13 days of the disease onset (early sample) and from the 14th day to death or hospital discharge (follow-up sample). Results: We studied 82 COVID-19 patients (59.5 ± 17.5 years, 54.9% male). Of these, 34 (41.5%) developed AKI. These patients presented higher SARS-CoV-2 viral load ( P = 0.03), higher frequency of diabetes ( P = 0.01) and death ( P = 0.0004). Overall, AKI patients presented significantly higher and sustained levels ( P < 0.05) of CCL-2, CCL-3, CCL-4, CXCL-8, CXCL-10, IFN-γ, IL-2, IL-6, TNF-α, IL-1Ra, IL-10 and VEGF. Importantly, higher levels of CCL-2, CXCL-10, IL-2, TNF-α, IL-10, FGFb, and VEGF were observed in AKI patients independently of death. ROC curves demonstrated that early alterations in CCL-2, CXCL-8, CXCL-10, IFN-γ, IL-6, IL-1Ra and IL-10 show a good predictive value regarding AKI development. Lastly, immune mediators were significantly associated with each other and with SARS-CoV-2 viral load in AKI patients. Conclusions: COVID-19 associated AKI is accompanied by substantial alterations in circulant levels of immune mediators, which could significantly contribute to the establishment of kidney injury.